FOXP3+ Regulatory T Cell Compartment Is Altered in Children With Newly Diagnosed Type 1 Diabetes but Not in Autoantibody-Positive at-Risk Children - Viisanen, Tyyne; Gazali, Ahmad M.; Ihantola, Emmi-Leena; Ekman, Ilse; Näntö-Salonen, Kirsti; Veijola, Riitta; Toppari, Jorma; Knip, Mikael; Ilonen, Jorma; Kinnunen, Tuure (Frontiers in Immunology, 2019)
The dysfunction of FOXP3-positive regulatory T cells (Tregs) plays a key role in the pathogenesis of autoimmune diseases, including type 1 diabetes (T1D). However, previous studies analyzing the peripheral blood Treg compartment in patients with T1D have yielded partially conflicting results. Moreover, the phenotypic complexity of peripheral blood Tregs during the development of human T1D has not been comprehensively analyzed. Here, we used multi-color flow cytometry to analyze the frequency of distinct Treg subsets in blood samples from a large cohort comprising of 74 children with newly diagnosed T1D, 76 autoantibody-positive children at-risk for T1D and 180 age- and HLA-matched control children. The frequency of CD4+CD25+CD127lowFOXP3+ Tregs was higher in children with T1D compared to control children, and this change was attributable to a higher proportion of naïve Tregs in these subjects. Further longitudinal analyses demonstrated that the increase in Treg frequency correlated with disease onset. The frequencies of the minor subsets of CD25+FOXP3low memory Tregs as well as CD25lowCD127lowFOXP3+ Tregs were also increased in children with T1D. Moreover, the ratio of CCR6-CXCR3+ and CCR6+CXCR3- memory Tregs was altered and the frequency of proliferating Ki67-positive and IFN-γ producing memory Tregs was decreased in children with T1D. The frequency of CXCR5+FOXP3+ circulating follicular T regulatory cells was not altered in children with T1D. Importantly, none of the alterations observed in children with T1D were observed in autoantibody-positive at-risk children. In conclusion, our study reveals multiple alterations in the peripheral blood Treg compartment at the diagnosis of T1D that appear not to be features of early islet autoimmunity.